Literatura – kultura – (kon)tekst - Rudaš, Jutka (Slavia Centralis, 2020)
Literature – culture – (con)textThis paper intends to show all the (con)texts in which Esterházy articulates new models of life and literature, and the aesthetic changes which rock the traditional concept of justice. It further shows the importance of intertextuality, according to which each "text is an intertext", and each text is a patchwork of quotations and the previous or environment-shaping culture. I also deal with the unique dance of these figures in the "Celestial Harmonies", as it is this kind of creativity and textuality that makes Esterházy’s texts work.
Keywords: postmodernism; intertextuality; referentiality; Culture Code